Days of heroin use predict poor self-reported health in hospitalized heroin users - Meshesha, Lidia Z. (2013)
This study examined associations between substance use behaviors and self-reported health among hospitalized heroin users. Of the 112 participants, 53 (47%) reported good or better health. In multivariable logistic regression models, each day of heroin use in the last month was associated with an 8% lower odds of reporting health as good or better (OR=.92; 95%CI 0.87, 0.97, p < .05). Cocaine, cannabis, cigarettes, alcohol use, unintentional overdose, nor injection drug use were associated with health status.